Hormonal changes in thalassaemia major. Issue 11 (November 1976) - Flynn, D M; Fairney, A; Jackson, D; Clayton, B E
Abstract : Patients with severe thalassaemia major suffer endocrine and other abnormalities before their eventual death from iron overload due to repeated blood transfusions. The endocrine status of 31 thalassaemic patients aged 2-5 to 23 years was investigated. Exact data were available on the rate and duration of blood transfusion in all of them and in many the liver iron concentration was also known. Although the patients were euthyroid, the mean serum thyroxine level was significantly lower, and the mean thyrotrophic hormone level significantly higher, compared with the values found in normal children. Forty oral glucose tolerance tests with simultaneous insulin levels were performed in 19 children, of whom 5 developed symptomatic diabetes and one had impaired tolerance. Previous tests on all 6 patients were available and some showed raised insulin levels possibly due to insulin resistance. 2 patients had clinical hypoparathyroidism and are described. The parathyroid hormone levels determined by radioimmunoassay in 25 patients were below the mean for the age group in all and outside the reference range in 16. Nonfasting plasma calcium levels were not reduced. Puberty was delayed in some patients. Concentrations of luteinizing hormone (LH) and follicle-stimulating hormone (FSH) measured in urine from 7 girls and 5 boys showed considerable variation. In the boys there was an overall tendency for FSH and LH excretion to be low with regard to age, but with respect to puberty rating FSH exretions were normal or low and LH normal or raised.The girls showed a tendency for LH but not FSH excretion to be raised in relation to puberty rating. The severity of the endocrine changes was related to the degree of iron loading and is discussed in relation to previous work in which the iron loading has rarely been accurately indicated nor parathyroid status assessed.